Penguatan Daya Saing Sektor Pertanian Barbasis Usaha Tani Skala Kecil; Review Literature - Silfia .; Helmi .; Melinda .; Henmaidi . (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
Agricultural competitiveness is a prerequisite to benefit from free trade. Increasing the competitiveness of agriculture can not be separated by the existence of small-scale farming because Indonesia's agricultural sector is dominated by cultivation activities conducted in small-scale units, inefficient, low productivity, low value added and low trading performance strategy is needed in improving the competitiveness of small scale farm-based. This review is a qualitative description presenting a review literature on the concept of competitiveness and the dynamics of agriculture based on small-scale farming and how to build competitivenessof small-scale farmer